2013
DOI: 10.2465/jmps.111229
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state luminescence measurement for qualitative identification of rare earth ions in minerals

Abstract: Minerals are the source of rare earth elements (REE), and knowledge of the amount of REE in different minerals is necessary for a mineralogist. We propose steady -state luminescence measurement as a quick and non -destructive method for detecting several lanthanide ions present together in the same sample. By using excitation and emission spectra of each 4f ion, rare earth ions could be easily identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…In the spectral range of 550-700 nm, the emission lines of these two ions are located close to each other and are: at 562 nm and 569 nm as 4 G5/2 → 6 H5/2 transition of Sm 3+ ; at 601 nm and 607 nm of both Sm 3+ 4 G5/2 → 6 H7/2 and Pr 3+ 1 D2 → 3 H4 + 3 P0 → 3 H6 transitions; and at 648 nm mainly for Pr 3+ transition 3 P0 → 3 F2. As it was found earlier [9], the most convenient excitation for Sm 3+ is the 399-402 nm line, while for Pr 3+ it is 480 nm (Figure 10). The photoluminescence spectra of Dy 3+ , Sm 3+ , and Pr 3+ and Ce 3+ .…”
Section: Energy Transfer Ce 3+ -Sm 3+ Pr 3+ and Eu 3+supporting
confidence: 72%
See 1 more Smart Citation
“…In the spectral range of 550-700 nm, the emission lines of these two ions are located close to each other and are: at 562 nm and 569 nm as 4 G5/2 → 6 H5/2 transition of Sm 3+ ; at 601 nm and 607 nm of both Sm 3+ 4 G5/2 → 6 H7/2 and Pr 3+ 1 D2 → 3 H4 + 3 P0 → 3 H6 transitions; and at 648 nm mainly for Pr 3+ transition 3 P0 → 3 F2. As it was found earlier [9], the most convenient excitation for Sm 3+ is the 399-402 nm line, while for Pr 3+ it is 480 nm (Figure 10). The photoluminescence spectra of Dy 3+ , Sm 3+ , and Pr 3+ and Ce 3+ .…”
Section: Energy Transfer Ce 3+ -Sm 3+ Pr 3+ and Eu 3+supporting
confidence: 72%
“…However, the emission bands of Er 3+ corresponding to the 2 H11/2 → 4 I15/2, 4 S3/2 → 4 I15/2 and 4 F9/2 → 4 I15/2 transitions and usually measured at a 500-600 nm range were not clearly visible for steady-state luminescence measurements using a xenon lamp excitation, contrary to time-resolved measurements [8]. It has previously been verified [9] that for steady-time measurements using a xenon lamp, the most convenient excitation for Er 3+ is λ = 377 nm. However, for the studied agrellite specimen, only a weak emission band at 543 nm was measured ( Figure 4).…”
Section: Nd 3+ Yb 3+ and Er 3+ Luminescencementioning
confidence: 90%
“…The primary excitation wavelength for Ce 3+ was λ exc =290 nm, according to our earlier studies (Czaja et al 2013). We subsequently verified that the recorded spectrum was correct, i.e., that we did not measure reflections from xenon lamp nor Raman shift.…”
Section: Methodsmentioning
confidence: 52%
“…Conventional fluorescence has previously been shown as a good qualitative measure of rare earth ion presence in fluorite, though as discussed previously emission can be quenched by energy transfer to other absorbing centres. 67 Another complication that has been noted is the spectral overlay of erbium and holmium emissions, both having visible peaks between 520 and 560 nm. 34 Our experiments have confirmed that conventional fluorescence with monochromatic laser light is suitable for exciting holmium and erbium emissions one at a time, though broader-band excitation sources may not enable distinguishing between the two.…”
Section: Erbium and Holmium Upconversion Fluorescence In Fluoritementioning
confidence: 99%